TEORI PENGOLAHAN INFORMASI DAN IMPLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - M Kasyful Anwar; Muhammad Agus Syahnginata; Haidar Hafiedz; Husni Idris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses the theory of information processing and its implications for Islamic Religious Education (PAI) learning. The study aims to analyze the basic concepts, stages, and implications of information processing theory in the learning process. This research employed a qualitative descriptive approach using library research methods. Data were obtained from scientific articles, books, journals, and other relevant references related to cognitive learning theory and Islamic education. Data collection techniques were conducted through documentation studies, while data analysis used content analysis techniques. The findings indicate that information processing theory views learning as an active mental process involving receiving, processing, storing, and retrieving information. The stages of information processing involve sensory memory, short-term memory, and long-term memory, supported by cognitive processes such as attention, encoding, storage, and retrieval. The application of information processing theory in PAI learning emphasizes student-centered learning, active learning strategies, structured material organization, the use of instructional media, and comprehensive evaluation. This theory contributes to improving students’ understanding, memory retention, critical thinking skills, and internalization of Islamic values in everyday life.